2004
DOI: 10.1073/pnas.0403201101
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging shows that insulin granule exocytosis occurs by complete vesicle fusion

Abstract: Confocal imaging of GFP-tagged secretory granules combined with the use of impermeant extracellular dyes permits direct observation of insulin packaged in secretory granules, trafficking of these granules to the plasma membrane, exocytotic fusion of granules with the plasma membrane, and eventually the retrieval of membranes by endocytosis. Most such studies have been done in tumor cell lines, using either confocal methods or total internal reflectance microscopy. Here we compared these methods by using GFP-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 27 publications
4
97
0
Order By: Relevance
“…Various studies have suggested that insulin granules undergo complete fusion resulting in the total mixing of granule membrane proteins and lipids with the plasma membrane (12)(13)(14). Alternatively, other studies have suggested that the insulin granules transiently open a fusion pore to allow intraluminal contents to diffuse out followed by membrane closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have suggested that insulin granules undergo complete fusion resulting in the total mixing of granule membrane proteins and lipids with the plasma membrane (12)(13)(14). Alternatively, other studies have suggested that the insulin granules transiently open a fusion pore to allow intraluminal contents to diffuse out followed by membrane closure.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies have suggested that the release of the insulin-containing dense core granule content occurs en masse, consistent with the formation of a plasma membrane pore that fully expands to encompass the granule membrane proteins and lipids (12)(13)(14). Alternatively, it has also been suggested that insulin granules may actually stack and communicate with each other with a given granule releasing its content into another granule leading to a continuously gating channel to the plasma membrane through a process called compound exocytosis (15,16).…”
mentioning
confidence: 99%
“…Importantly, this distinction between "full" but reversible events versus complete merger is difficult, if not impossible to detect, unless the fates of membrane and cargo markers are imaged simultaneously [81,109]. This limitation may explain why recordings relying solely on soluble probes [112,113] tend to invoke complete vesicle merger as the principal mechanism of insulin release.…”
Section: Mechanisms Of Vesicle Release At the Cell Surface: Full Fusimentioning
confidence: 99%
“…Cells were then harvested and purified using CsCl gradient ultracentrifugation (50), and viral titers were measured by the formation of viral plaques in sequential dilutions. Replicationdeficient Ad constructs were used: Ad-syncollin-GFP (kindly provided by Dr. Christopher Rhodes, University of Chicago) (20,27) and Ad-GFP (53). Mouse Rab27 sequences, fused to epitope tags on their NH 2 termini, were expressed using the following constructs: Ad-Xpress-Rab27bQ78L (constitutively active; Xp-CA), Ad-Xpress-Rab27bN133I (dominant negative; Xp-DN) and AdXpress-Rab27b (wild-type; Xp-WT), which were kind gifts of Dr. John Williams, University of Michigan (6,56); and Ad-YFPRab27b (YFP-WT), Ad-YFP-Rab27bQ78L (YFP-CA), Ad-YFPRab27bN133I (YFP-DN) as described (43).…”
Section: Methodsmentioning
confidence: 99%